Tinjauan Yuridis Perjanjian Pra Nikah Dalam Perspektif Hukum Islam dan Hukum Positif Indonesia - Nuyun Nurillah (Jurnal Ilmiah Wahana Pendidikan, 2023)
Marage between a man and a woman has physical and spiritual ramifications for the family and the possessions earned before and during the marriage. Before marrying, a prospective husband and wife may create a marriage agreement, also known as a pre-nuptial agreement. This research aims to 1) determine the terms of the pre-nuptial agreement under Islamic Law and Indonesian Positive Law, and 2) determine the legal repercussions of violating the prenuptial agreement under Islamic Law and Indonesian Positive Law. This normative study takes a legislative, conceptual, and comparative approach. The data collection methodology employed in this study was library research, and the analysis method was a descriptive qualitative method. According to the findings of this study, the legal rules of pre-nuptial agreements are governed in the Civil Code Articles 139-154. Marriage agreements are regulated in Book I Chapter VIl of the Compilation of Islamic Law (KHI), commencing from articles 45-52. The marriage contract cannot be modified unless both parties agree. According to the Civil Code, a marriage agreement must be made with a notarial deed before the marriage. In Islamic, and positive law, it is said that if the marriage agreement is violated, the husband or wife who cannot tolerate the circumstances may petition for divorce or compensation.